Integrated weed control options under different sowing methods of isabgol (Plantago ovata Forsk) at transitional luni basin plain zone of Rajasthan - Reager, M.L.; Deora, N.S.; Tak, S.R.; Sanwal, R.C. (Annals of Agricultural Research, 2017)
A field experiment was conducted during rabi season of 2011-12 and 2012-13 at farmer's fields andKrishi Vigyan Kendra, Jalore to study the effect of sowing methods and weed control optoins inisabgol. The experiment was laid out in a split-plot design with five replications. The treatmentsconsisted of three main plots (sowing methods- broadcasting, sowing in line at 30 cm and sowing inline at 22.5 cm) and three sub plots (control, hand weeding at 30 DAS and post emergence applicationof isoproturon 600 g ha–1 at 20 DAS +hand weeding at 30 DAS). Sowing of isabgol cv. RI- 89 wasdone as per the sowing methods as broadcasting and different row spacing. Post emergence aplicationof isoproturon at 20 DAS + hand weeding at 30 DAS in line sowing at 22.5 cm row spacing havingstatistically at par with hand weeding at 30 DAS in line sowing at 22.5 cm row spacing producedsignificantly maximum seed yield (1275.8 kg ha–1), straw yield (2665.1 kg ha–1) and net return (Rs59392/- ha) over other weed control treatments in broadcast sowing and line sowing at 30 cm aswell as 22.5 cm. However, in broadcast sowing, post emergence application of isoproturon at 20DAS + hand weeding at 30 DAS enhanced seed, straw and net return over hand weeding at 30 DASand unweeded control.